Combination Of Breast Care And Oxytocin Massage Of Breastfeeding Mothers In Infant Weight Gain - Ria Gustirini; Inge Anggi Anggraini (poltekkes kemenkes mataram, 2020)
The perception that the supply of milk production is less than 30-80% of breastfeeding mothers is the main reason mothers stops breastfeeding their babies. Breast milk is a source of fat and protein that is important for the growth and nutrition of infants. Increased breast milk secretion has a very positive impact on the baby's weight gain. One technique to increase milk production, among others, by doing breast care and oxytocin massage. Breast Care aims to expedite blood circulation and prevent blockage of milk production channels from facilitating the expenditure of milk. At the same time, oxytocin massage can stimulate the secretion of the hormone oxytocin (letdown reflex) so that milk comes out. This research analyzes the effect of a combination of breastcare and oxytocin massage on breastfeeding mothers on infant weight gain. This research is a quasi-experimental study with a pre-post test control design. Sampling took as consecutive sampling. The results showed that there were significant mean differences in infant weight gain between the treatment and control groups (p <0.05). The results of this study expected to contribute to midwifery as a non-pharmacological effort to increase milk production which will have a positive impact on infant weight so that it can support the government's efforts to increase exclusive breastfeeding coverage and reduce infant mortality and morbidity.